Tourism Communication Model in Developing Heritage City Tourism in Siak Sri Indrapura Regency, Riau, Indonesia - Noor Efni Salam; Yasir Yasir; Muhammad Firdaus; Rusmadi Azwa; Evawani Elysa Lubis (Yayasan Adra Karima Hubbi, 2024)
Background. Siak Sri Indrapura in Riau is one of the heritage city areas in Indonesia. Its main pillars include historical and cultural heritage such as the kingdom with its artifacts, traditional halls, mosques, traditional arts and crafts, and culinary. With this potential, Siak Sri Indrapura Regency has become a destination that many tourists visit to improve the economy of its community. Purpose. This study aims to explain communication patterns in developing heritage cities as tourist destinations in Siak Regency. Method. This research uses stakeholder theory with a tourism and heritage tourism communication approach, and uses qualitative methods. Results. The results of the study show that local governments supported by the private sector/entrepreneurs, academics, media, and local communities implement communication patterns in developing heritage tourism. Local governments play an active role in developing heritage tourism by taking formal legal protection for various heritage sites; the private sector/entrepreneurs have encouraged and accelerated government programs through capital assistance; academics have supported the government through research activities; the media has distributed information related to heritage tourism; and the local community is the axis and actor in the development of heritage tourism in Siak. Conclusion. The pattern of tourism communication in developing heritage cities as tourist destinations begins with a balanced relationship between the government and related parties, expanding private and academic functions, increasing the role of the media, and strengthening local communities as actors in the development of Siak as a heritage city. Therefore, this tourism communication pattern can be a role model for other regions to develop sustainable heritage tourism.